Phylogenetic analysis of coccidian parasites from invertebrates: search for missing links - Kopecná, Jana; Jirků, Milan; Oborník, Miroslav; Tokarev, Youri S; Lukes, Julius; Modrý, David (Protist, 2006)
Apicomplexan parasites represent one of the most important groups of parasitic unicellular eukaryotes comprising such important human parasites such as Plasmodium spp. and Toxoplasma gondii. Apicomplexan radiation as well as their adaptation to the parasitic style of life took place before the era of vertebrates. Thus, invertebrates were the first hosts of apicomplexan parasites that switched to vertebrates later in evolution. Despite this fact, apicomplexan parasites of invertebrates, with the exception of gregarines, have so far been ignored in phylogenetic studies. To address this issue, we sequenced the nuclear SSU rRNA genes from the homoxenous apicomplexan parasites of insects Adelina grylli and Adelina dimidiata, and the heteroxenous Aggregata octopiana and Aggregata eberthii that are transmitted between cephalopods and crustaceans, and used them for phylogenetic reconstructions. The position of the adelinids as a sister group to Hepatozoon spp. within the suborder Adeleorina was stable regardless of the phylogenetic method used. In contrast, both members of the genus Aggregata possess highly divergent SSU rRNA genes with an unusual nucleotide composition. Because of this, they form the longest branches in the tree and their position is variable. However, the genus Aggregata branches together with adelinids and hepatozoons in most of the analyses, although their position within the scope of this cluster is unstable.
Keywords: Evolution, Molecular; Mollusca; molekulární evoluce; molekulární sekvence - údaje; Genes, rRNA; Arthropods; členovci; geny rRNA; měkkýši; Animals; Phylogeny; Coccidia; zvířata; fylogeneze; Molecular Sequence Data